Development and Psychometrics of a Questionnaire to Assess the Importance of Integrated Education in Undergraduate Nursing from the Perspective of Faculty Members - Ali Toghyani; Jahanbakhsh Rahmani; Shayesteh Salehi; Marzieh Adelmehraban (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Despite the importance of integrated education in nursing, limited studies have been conducted to develop appropriate tools to assess its importance in Iran. Objectives: The present study aimed to develop a questionnaire and psychometrically assess the importance of integrated education in nursing from the perspective of faculty members. Methods: This is a consecutive exploratory mixed study conducted in two stages. In the first stage, the concept of Intergrated training was explained via qualitative theme analysis and the relevant key themes of the identification articles were coded. Sampling was purposeful and continued until saturation. In the second (quantitative) stage, first the face and content validity was reviewed and the necessary corrections were made by 15 experts. Then, the reliability of the questionnaire was calculated using internal consistency method (Cronbachchr('39')s alpha) and the construct validity of the instrument was calculated using exploratory factor analysis. Results: 203 items were extracted via qualitative content analysis and review of related scientific texts. After performing face and content validity (qualitative and quantitative) 162 items remained. Exploratory factor analysis led to the removal of 50 items and thus 112 items in 4 factors (dimension or scope), including educational content, educational activities, context and conditions. An evaluation was extracted which explained these 4 factors of 87.774 of the total variance. The reliability of the instrument with Cronbachchr('39')s alpha was 0.92. Conclusion: The questionnaire on the feasibility of the integrated curriculum in the field of nursing with features such as reliability and validity can be easily used by faculty members and policy makers. It is suggested that other psychological features of the instrument such as convergent and divergent validity be examined in future studies